(Ri)uso dei plurali divini nella redazione deuteronomistica dell'episodio del Carmelo (1Re 18) - Campi, Giorgio Paolo (Henoch, 2022)
This article deals with the use of morphological plurals in divine names and titles within 1Kings 18. The passage, as part of the Elijah Cycle, displays the contest between Elijah and the prophets of Baal on Mount Carmel. Initially, some considerations are presented on the Deuteronomistic redactional activity on the passage and on the meaning of the term האלהים / אלהים, which is used here as a title reserved to Israel’s national deity. A Deuteronomistic redactional suture is then identified at 1 Kings 18:18b-19. These vv. contain the only appearance of the plural בעלים in the whole passage. It is then sho- wed how the insertion of this plural בעלים, along with its relationship with האלהים / אלהים and the singulars Baal and YHWH, radically changes the ideological implications and reshapes the meaning of the passage. Thank to a conscious use of plurals in the narrative, the Deuteronomistic writer(s) provides a new theological reading of the passage. The Deuteronomist’s vision introduces a monolatric perspective: the theological focus shifts from the contest to determine the identity of Israel’s national deity to Israel’s recognition of YHWH as its one true god.